EVA1B facilitates esophageal squamous carcinoma progression and recruitment of immunosuppressive myeloid-derived suppressor cells in the tumor microenvironment - Tian Xia; Yongkang Zhang; Haodong Peng; Xiangbo Jia; Dong Yang; Li Wei; Tian Li; Wenjian Yao (Elsevier, 2024)
Eva-1 Homolog B (EVA1B) has been preliminarily found to be associated with prognostic outcomes and immune microenvironment in several human cancer types, but the implications of EVA1B in ESCC remain unclear. Human ESCC and paracancerous tissues were gathered in this study, and EVA1B expression was measured via immunoblotting. EC109 and KYSE-180 ESCC cells were stably infected by sh-EVA1B lentivirus, and functional experiments were subsequently implemented. Syngeneic mouse models were built, and the expansion and recruitment of myeloid-derived suppressor cells (MDSCs) were then evaluated. The results showed that EVA1B presented the notable up-regulation in clinical ESCC tissues versus controls, and was connected to more advanced stages and the abundance of MDSCs. Silencing EVA1B notably attenuated proliferation of ESCC cells and tumor growth in syngeneic mouse models. Moreover, EVA1B suppression resulted in apoptosis and cell cycle arrest, and impaired ESCC cell aggressiveness. Among ESCC patients, EVA1B was strongly correlated to EMT pathway activity. Targeted suppression of EVA1B mitigated the expression of Wnt3a, β-catenin and LRP6 in ESCC cells and tumor xenografts. Additionally, inhibition of EVA1B attenuated the expansion and recruitment of MDSCs within the immune microenvironment based upon the reduction in the percentage of CD11b+Gr-1+ immunosuppressive MDSCs as well as the expression of MDSC expansion stimulators (S100A8, S100A9, Arg-1, and VEGF). Collectively, our findings unveiled the contribution of high expression of EVA1B to ESCC progression and MDSCs expansion and recruitment, indicating that targeted suppression of EVA1B may be a potential treatment choice for ESCC patients.